Current T1 and T2 mapping techniques applied with simple thresholds cannot discriminate acute from chronic myocadial infarction on an individual patient basis: a pilot study. Issue 1 (December 2016) - von Knobelsdorff-Brenkenhoff, Florian; Prothmann, Marcel; Dieringer, Matthias; Wassmuth, Ralf; Rudolph, André; Utz, Wolfgang; Traber, Julius; Greiser, Andreas; Niendorf, Thoralf; Schulz-Menger, Jeanette
Abstract Background Studying T1 - and T2 -mapping for discrimination of acute from chronic myocardial infarction (AMI, CMI). Methods Eight patients with AMI underwent CMR at 3 T acutely and after >3 months. Imaging techniques included: T2 -weighted imaging, late enhancement (LGE), T2 -mapping, native and post-contrast T1 -mapping. Myocardial T2 - and T1 -relaxation times were determined for every voxel. Abnormal voxels as defined by having T2 - and T1 -values beyond a predefined threshold (T2  > 50 ms, native T1  > 1250 ms and post-contrast T1  < 350 ms) were highlighted and compared with LGE as the reference. Results Abnormal T2 -relaxation times were present in the voxels with AMI (=> delete acute infarction; unfortunately this is not possible in your web interface) acute infarction only in half of the subjects. Abnormal T2 -values were also present in subjects with CMI, thereby matching the chronically infarcted territory in some. Abnormal native T1 times were present in voxels with AMI in 5/8 subjects, but also remote from the infarcted territory in four. In CMI, abnormal native T1 values corresponded with infarcted voxels, but were also abnormal remote from the infarcted territory. Voxels with abnormal post-contrast T1 -relaxation times agreed well with LGE in AMI and CMI. Conclusions In this pilot-study, T2 - and T1 -mapping with simple thresholds did not facilitate the discrimination of AMI and CMI.